Studi Penggunaan Kombinasi Obat Fenitoin dan Natrium Valproat terhadap Serum Magnesium dan Jumlah Kejang pada Pasien Epilepsi di RSUD DR. Soetomo - Sambono, Vonneth Glorya; Sugianto, Paulus; Kasih, Elisabeth; Octavia, Evi (Jurnal Farmasi Sains dan Terapan (Journal of Pharmacy Science and Practice), 2020)
Epilepsy is a clinical condition that is recognized by the pattern of seizures ranging from neurological development status according to age, history of seizures, and prognosis. Clinical research in humans and animals shows that magnesium deficiency can cause seizures. Drug therapy in epilepsy patients can be done by monotherapy and polytherapy. The combination of phenytoin and sodium valproate can be used as a polytherapy. The purpose of this study was to describe the serum magnesium levels and the number of seizures in epilepsy patients who received phenytoin and sodium valproate using a descriptive method prospectively. The parameters used are the conditions of the patient while receiving treatment. Ten epilepsy patients which treated with combination therapy of phenytoin and sodium valproate were used for this research.The results showed that the highest dose used in polytherapy was phenytoin 500 mg and sodium valproate 500 mg 2 x 1 po. The highest normal magnesium level was 2.21 mg / dL (10%). The highest number of seizures was 7 times a month (10%) and no adverse drug interactions occured. Phenytoin and sodium valproate therapy can minimize the number of seizures but do not affect the patient's magnesium level.